The Illness Patterns and Their Costs Among Hospitalized Elderly Covered by Medical Service Insurance Organization, in Damghan\'s Hospitals, in Year of 2005-2006 - Abolghasem Poor Reza; Majid Mir Mohammadkhani; Behrooz Pooragha (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: The increase of life expectancy, in spite of its satisfactory and hopeful impressions, has resulted to some problems and difficulties, in the last years of life, particularly with regard to the health, illness, and costs of services of elderly populations. In literature focused on epidemiologic transition, the change on patterns of disease widely discussed. But there is a lack for a detailed analysis to clarify the priorities of providing and consuming services in relation to a specific cronic illnesses and socio-economic and demographic characteristics of service users. For this purpose, and in order to identify the indications of epidemiologic transition, case studies and surveys are needed. The present study mainly focus on this goal to identify which services are used by which groups of elderly population, and on what costs? Methods & Materials: This study conducted in Damghan city in Semnan province. All patients over 60 years old, covered by Medical Services Insurance Organization (MSIO), hospitalized in Damghan>s hospitals (2 hospitals), during year 2006, selected as study population. Medical records of the study population reviewed and analysed. Results: Findings revealed that heart disease and blood system disfunctionning, was the major cause of hospitalization. Conclusion: The most frequent surgeries conducted for Catarakt , and the highest cost belonged to psychology and psychiatrist services.